Attitude on euthanasia of general practice nursing students of Alytaus kolegija / University of Applied Sciences - Valčiukienė, Lina; Prieskienytė, Diana; Paškevičė, Alma (Slauga. Mokslas ir praktika, 2023)
Summary. The article reveals the attitudes of general nursing students of Alytaus kolegija / University of Applied Sciences towards euthanasia. The last two decades of this century have seen an increasing number of countries where euthanasia has become legal, which has led to a growing number of disagreements between the health care community, politicians, society, and religion, and to ethical dilemmas around the world on this issue. Euthanasia has become a topical phenomenon that has so far generated countless debates and controversies in politics, law, medicine and society at large. This article presents the views of general nursing students on euthanasia, its legalisation and the reasons that have influenced their opinions. The study used a quantitative questionnaire survey method. The sample of the study was a purposive sample of general nursing students of the 1st and 4th year of the Department of Health Sciences and Technologies of Alytaus kolegija / University of Applied Sciences. Summarising the results obtained, it emerged that almost half of both 1st and 4th year students express a neutral attitude towards euthanasia, and more than half of both 1st and 4th year students support legalisation of euthanasia in Lithuania.
Keywords: nursing students; euthanasia; attitudes; death